Inclusive Communicative Strategies in an ESP Classroom: A Case Study at a Ukrainian University - Yuliana Lavrysh; Iryna Simkova; Kateryna Tuliakova (English Studies at NBU, 2022)
This paper describes the experience of Ukrainian educators in the promotion of social inclusion for internally displaced students. Attention is paid to the analysis of key notions and concepts of social inclusion in education, and the challenges associated with the implementation of inclusion strategies. This paper investigates the advantages and disadvantages of inclusive communication strategies implementation in ESP courses. The choice justified by its communicative orientation and focus on social interaction. One hundred and ten internally displaced students and fifteen ESP teachers participated in the study. The study presents the results gained from interviews with Ukrainian students and ESP teachers from Igor Sikorsky Kyiv Polytechnic Institute. A comparative analysis revealed the positive dynamics in internally displaced students' well-being after the implementation of inclusive communicative strategies. The findings support the idea that the well-being of internally displaced students can be improved with the implementation of individualization, diversification, and differentiation integrated into the ESP classroom.